Synthesis of Zinc Oxide Nanoparticles for Oil Upgrading and Wax Deposition Control: Effect of Calcination Temperature - Siti Nurliyana Che Mohamed Hussein; Fatin Syahirah Mohamed Fuad; Marina Ismail (Indonesian Journal of Chemistry, 2020)
In this study, ZnO nanoparticles were synthesized using a sol-gel method for oil upgrading and wax deposition control. The synthesized ZnO nanoparticles were used to measure viscosity and wax deposition in the heavy crude oil and to investigate the effectiveness of the nanoparticles in the reduction of viscosity and wax deposition control of the heavy crude oil. This study investigated the effect of calcination temperature on ZnO nanoparticles during synthesis towards viscosity reduction and wax deposition control. ZnO nanoparticles were calcined at different temperatures ranging from 300 to 900 °C. The calcined ZnO nanoparticles were characterized using X-ray diffraction (XRD), Field Emission Scanning Electron microscope (FESEM), and Energy-dispersive X-ray spectroscopy (EDX) for its structure, size, shape, and morphology. The characterization results showed a hexagonal wurtzite structure of ZnO nanoparticles. The physical properties and rheology of heavy crude oil were characterized by using Electronic Rheometer and cold finger method to analyze the viscosity, shear rate, and wax deposition of the heavy crude oil for performance study. Decreased in crystallite size from 15.59 to 12.84 nm was observed with increasing calcination temperature from 300 to 400 °C, and a further increase of calcination temperature from 400 to 900 °C, the crystallite size increased from 12.84 to 41.58 nm. The degree viscosity reduction (DVR %) of heavy crude oil was observed to increase by 41.7%, with decreasing ZnO nanoparticles size from 30.11 nm to 12.84 nm. The optimum calcination temperature was 400 °C. Wax deposition decreases by 32.40% after the addition of ZnO nanoparticles into heavy crude oil.